A Phase II, Multicenter, Randomized, Placebo-Controlled Study of Benralizumab, a Humanized Anti-IL-5R Alpha Monoclonal Antibody, in Patients With Eosinophilic Chronic Rhinosinusitis. Issue 6 (November 2021) - Takabayashi, Tetsuji; Asaka, Daiya; Okamoto, Yoshitaka; Himi, Tetsuo; Haruna, Shinichi; Yoshida, Naohiro; Kondo, Kenji; Yoshikawa, Mamoru; Sakuma, Yasunori; Shibata, Kunihiko; Suzuki, Motohiko; Kobayashi, Masayoshi; et al.
Background: Strong eosinophil infiltration in chronic rhinosinusitis with nasal polyp (CRSwNP) is highly associated with recalcitrance and higher nasal polyp recurrence rate after surgery. The prevalence of eosinophilic CRSwNP (ECRS) is increasing in Asian countries including Japan. Benralizumab is a humanized anti-IL-5R alpha monoclonal antibody that depletes eosinophils by antibody-dependent cell-mediated cytotoxicity. Objective: To assess the efficacy and safety of benralizumab in patients with ECRS. Methods: This phase II, randomized, double-blind, placebo-controlled study was conducted in Japan. Patients were randomized 1:2:2 to placebo, a single administration of benralizumab 30 mg, or benralizumab 30 mg every 4 weeks (q4w) for a total of three doses. The primary endpoint was the change in nasal polyp score from baseline at Week 12. Results: Overall, 56 patients were enrolled (placebo, n = 11; benralizumab single dose, n = 22; benralizumab q4w, n = 23). Although the mean total nasal polyp score began to decrease after the initiation of benralizumab treatment, there were no statistically significant differences in change in nasal polyp score from baseline at Week 12 between benralizumab and placebo (placebo, −0.5 ± 0.8; benralizumab single, −0.3 ± 0.8; benralizumab q4w, −0.5 ± 1.5). Post-hoc analysis showed that the administration of benralizumab decreased nasal polyp scores ≥2 points in 42.2% of ECRS patients and that patients with high blood eosinophil levels had a greater tendency to respond to benralizumab treatment. The safety profile was similar to that in previous studies and no unexpected adverse events were noted. Conclusion: Although benralizumab did not meet the primary efficacy endpoint, reductions of nasal polyp scores were seen in the benralizumab group compared with the placebo group over the whole study period, especially in patients with high levels of blood eosinophils.